PROPERTY OWNERSHIP OF HOUSING UNITS IN FLAT (SRS) BY LAW NUMBER 20 OF 2011 ON FLAT - J. Salamat Tambunan,; Bambang Heri Supriyanto,; MuhammarAmin, (International Journal of Social Science, 2024)
Property rights in the ownership of residential apartment units are primarily low-income communities (MBR) as one manifestation of the state's responsibility to provide the necessities of shelter for citizens who are less able. Government in this case as the State's executive constantly strive to fulfill the responsibility in order to meet as it has been mandated in legislation such as the Law of 1945, Law No. 20 of 2011 on flats. In this paper the authors try to explain the issues are: with regard to who has the right to own and occupy the flats then the ownership of flats and remedies, issues related to the ownership of flats. It can be concluded with regard to the ownership of residential apartment units not only be owned by the private but also by legal entities that are qualified and applicable regulations and that has been determined, then in the process of ownership the government has given laws and regulations in order to become a reference in making ownership of the residential apartment units later in the execution occur the problems that arise then the government gives space settlement efforts both litigation and non litigation, known as a win-win solution that is expected mantinya not detrimental to both sides especially to low-income people who harmed